REVIEWING INTERNATIONAL PATENT POLICY ON BIOTECHNOLOGICAL INVENTIONS AND THE ADEQUACY OF EQUITABLE BENEFIT SHARING PRINCIPLE (UUM Journal of Legal Studies, 2020)
The purpose of this study is to review international patent policy related to biotechnological inventions, particularly from the Venetian Patent Law to the TRIPs Agreement. It closely examines whether such inventions fulfill the patentability thresholds and analyses the reason why such patents are regarded as having the potential to cause facility misappropriation of biodiversity, which is considered unfair. The most important part of this study is the adequacy analysis of the principles of equitable benefit sharing of the Convention on Biodiversity (CBD), including disclosure requirements and prior informed consent (PIC), to prevent misappropriation of biological resources in this era of fourth industrial revolution. This study is based on normative legal research method and uses primary and secondary legal resources. The analysis conducted for this study employed several approaches, which are: statute, conceptual, and historical approaches. This study found that patent protection for biotechnological inventions has received justification since the Paris Convention. However, the current international patent policy has a potential to facilitate misappropriation of biodiversity and it is regarded as unfair. On the other hand, equitable benefit sharing principle is still inadequate in dealing with such misappropriation. It advises the requirement of mandatory disclosure of origin to be regulated under national law as a legal basis for implementing equitable benefit sharing principle.